Effects of Time-Dependent Protein Restriction on Growth Performance, Digestibility, and mTOR Signaling Pathways in Juvenile White Shrimp Litopenaeus vannamei - Zhao, Wei; Luo, Hongjie; Zhu, Wanqing; Yuan, Xiaoqin; Shao, Jianchun (Frontiers in Physiology, 2021)
A 6-week feeding strategy experiment was conducted to investigate the effects of time-dependent protein restriction and subsequent recovery on shrimp. 43% and 36% protein level diets were used as adequate and restricted diet, respectively. Shrimp with initial body weight of 6.52 ± 0.46 g was conducted with four feeding strategies: feeding adequate diet for six weeks (T1, the control), feeding protein-restricted diet in week 1 and 4 (T2), feeding protein-restricted diet in week 1, 3 and 5 (T3) and feeding protein-restricted diet in week 1, 2, 4 and 5 (T4). WG, SGR, FE and PER of shrimp in T1-T3 showed no significant difference (P > 0.05), these indicators of T4 were significantly reduced (P < 0.05). No significant differences were found in digestive enzyme activities of shrimp among all treatments (P > 0.05). Crude protein contents of shrimp muscle in T4 was lower than that of T1-T3. The expression level of tor in T4 was lower than that in other treatments, while 4e-bp was higher than that of other treatments. To balance saving feed cost and growth performance, feeding protein-restricted diet in 1 week with subsequent realimentation (T2 and T3) is suitable for shrimp under high density conditions.